Perencanaan Ulang Saluran Drainase Berwawasan Lingkungan pada Kelurahan Kedundung Kota Mojokerto - Putri, Benedicta Aldora; Zenurianto, Mohamad; Hanggara, Ikrar (Journal of Civil Engineering, 2025)
Kedungdung Village, Mojokerto City is an area prone to flooding during the rainy season, because the drainage channels in the area were built several years ago so that some parts are damaged, overgrown with grass or clogged with garbage so that the channels do not function properly and cause water to overflow. Therefore, in this area, it is necessary to redesign the environmentally friendly drainage system with the aim of increasing water absorption and reducing the risk of flooding. The data required in this study are the results of field surveys, location maps, rainfall data from Gedeg, Pasinan and Terjunan stations, topographic maps, and unit work prices (HSPK) of Mojokerto City 2023. Data processing was carried out using the Gumbel method, and then a suitability test was carried out using the Chi-Square and Smirnov-Kolmogorov methods with a 5-year recurrence period. To analyze the water level in existing channels and planned channels, HEC-RAS software was used. Planning includes redesigning several channels by enlarging the size of the channels. From the calculation results, the design rainfall was obtained as 73,957 mm/day; The design flood discharge in the channel varies from 0.0001 m3/second to 0.0278 m3/second; the infiltration well is planned with a diameter of 50 cm and a depth of 200 cm; from the analysis using the HEC-RAS software program, it is known that 3 channels overflowed out of 39 channels analyzed; the total cost required in planning the drainage channel and infiltration well is Rp 1,096,728,000.00